Implementasi Sistem POS Pada Kedai Kopi Semper Berbasis Odoo - Otniel, Kevin; Abdillah, Lufty (UNIVERSITAS KALBIS, 2024)
Semper Coffee is an UMKM business that focuses on the food and beverage sector. Semper Coffee is a cafe business that still applies a manual system and does not yet have a system for its business sales process. This can lead to wrong recording for the documentation of each sales transaction. Therefore, by implementing ERP in Kopi Semper's business processes, it is expected to increase Kopi Semper's activities in order, sell and make documentation. Enterprise Resource Planning (ERP) is a system created to help business process activities more accurately and integrated. Point of Sale (POS) is an ERP-integrated Odoo application. POS is a system that is widely used by various retail businesses to make buying and selling transactions. Therefore, it is hoped that by using the Odoo ERP application which can help business processes at Kopi Semper so that every buying and selling transaction carried out by the purchasing department can be well documented. The waterfall method is the fastest and most efficient ERP implementation for the final project.